2021
DOI: 10.1002/er.6469
|View full text |Cite
|
Sign up to set email alerts
|

Improved photovoltaic properties of dye sensitized solar cell by irradiations of Ni 2+ ions on Ag‐doped TiO 2 photoanode

Abstract: Using the dip-coating technique we report here the synthesis of pure and 1% Ag-doped TiO 2 thin films. The 1% Ag-doped TiO 2 films are then irradiated with Ni ions at different (2 × 10 14 , 4 × 10 14 , and 6 × 10 14 ions/cm 2 ) fluences. Structural analysis carried out using the X-ray diffraction technique revealed the evolution of anatase phase in addition to rutile traces. The corresponding lattice parameters (a and c) first increases with doping and irradiation of Ni ions up to 4 × 10 14 ions/cm 2 which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…These curves were used to calculate the photovoltaic parameters of the pure and Ag-irradiated MAPbBr 3 -based solar cells such as the short circuit current density ( J sc ), conversion efficiency ( η ), open-circuit voltage ( V oc ), and fill factor ( FF ), as summarized in Table 3 . To determine the power conversion efficiency, the Equation (12) was used [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…These curves were used to calculate the photovoltaic parameters of the pure and Ag-irradiated MAPbBr 3 -based solar cells such as the short circuit current density ( J sc ), conversion efficiency ( η ), open-circuit voltage ( V oc ), and fill factor ( FF ), as summarized in Table 3 . To determine the power conversion efficiency, the Equation (12) was used [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…TiO 2 is a transition metal-oxide semiconductor, [102,103] predominantly used in photo-catalytic, [104][105][106][107][108] photo-electrochemical water splitting, [109][110][111][112] and photo-voltaic [12,[113][114][115] applications. A good description of TiO 2 can be found in the reviews.…”
Section: Titanium Dioxide (Tio 2 )mentioning
confidence: 99%
“…The coated substrate was subsequently placed in an oven for a specific period and at a specific temperature to expedite the evaporation of the solvent and the crystallization of the CsPbIBr 2 coating. 11…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that doping, a commonly used process in semiconductor technology, offers a promising way to enhance the structural and optoelectronic characteristics of perovskite materials. 11 Doping has the capability to augment stability, optimize the mobility of charge carriers, and alter the band structure, consequently heightening the effectiveness of solar cells. Tan et al replaced Cs positions in order to improve crystallinity and structure, in conjunction with the less massive monovalent alkali metal ion Li + .…”
Section: Introductionmentioning
confidence: 99%